(untitled) (Terr@ Plural, 2019)
In recent years, Dengue has become a serious public health problem for the Brazilian population, especially in urban environments. The disease is directly related to the proliferation and infestation index of the vector, which in turn depends on environmental factors that drive to its multiplication. In this sense, this study aimed to understand the causes of the significant increase of Dengue in Mato Grosso in the period between 2011 and 2015. So, we analyzed the temporospatial variation of cases of Dengue notifications provided by the State Department of Health, in order to investigate the hypothesis that such an expressive increase of the disease in this period could be related, above all, to socio-environmental conditions. It can be seen through the study that in the last few years there has been an alarming increase in the rates of dengue in most of the municipalities of the state of Mato Grosso and in all sectors of the territory of the state, and in those in which The weathering rate has been very different.